Study of processing, microstructure and mechanical properties of hot rolled ultra-high strength steel. (3rd July 2019) - Zhou, Tihe; Overby, David; Badgley, Peter; Martin-Root, Chris; Wang, Xiang; Liang, Shenglong; Zurob, Hatem
ABSTRACT: Hot rolled ultra-high strength steel with a gauge range of 3–10 mm (0.118¨–0.395¨) was developed using conventional slab caster and hot strip mill technology at Stelco Inc. (Stelco) to meet standard industry specifications along with additional unique customer requirements. The effects of chemical composition, steelmaking and hot rolling process parameters on microstructure, precipitation behaviour, and mechanical properties were studied. Both Grade 90 (620 Mpa, Stelco trademarked STELMAX TM 90) and Grade 100 (690 MPa, STELMAX TM 100) products met strength requirements in longitudinal and transverse directions. Furthermore, these ultra-high strength steels exhibited excellent ductility, impact toughness, edge stretchability and bendability. The enhanced mechanical properties are the results of chemistry design and carefully controlling austenite/ferrite grain size and precipitation behaviour at different processing stages. These newly developed steels have extensive applications in automobile safety components, light-weight construction, piping/tubing and offshore structures.